Risk Factors for the Development of Postembolization Syndrome after Transarterial Chemoembolization for Hepatocellular Carcinoma Treatment - Lima, Mariana (2018)
Introduction: Hepatic transarterial chemoembolization is a widely used technique for the treatment of hepatocellular carcinoma. The most common complication of this procedure is postembolization syndrome. The main objective of this study was to assess risk factors for the development of postembolization syndrome.Material and Methods: Single-centre retrospective analysis of 563 hepatic transarterial chemoembolization procedures from January 1st, 2014 – December 31st, 2015. Hepatic transarterial chemoembolization was performed with ½ - 2 vials of 100 - 300 μm microspheres loaded with doxorubicin. Patients who experienced postembolization syndrome were identified based on prolongation of hospitalization due to pain, fever, nausea and/or vomiting. A control group with the patients who did not have postembolization syndrome was randomly created (three controls for one case). Descriptive analysis and multivariate logistic regression were performed.Results: The overall prevalence of postembolization syndrome was 6.2%. Hepatic transarterial chemoembolization with doxorubicin dosage above 75 mg (more than one vial), the size of the largest nodule and female gender had statistically significant relation with development of postembolization syndrome (p = 0.030, p = 0.046 and p = 0.037, respectively). Discussion: Doxorrubicin dosage above 75 mg is associated with a higher risk of postembolization syndrome. This result can be helpful for decision-making in clinical practice, whenever it is possible to avoid a higher dose without compromising the efficacy of the treatment. The size of the largest nodule and female gender also constitute risk factors for postembolization syndrome. The other variables studied were not related to the development of postembolization syndrome.Conclusion: The dose of doxorrubicin, the size of the largest nodule treated and female gender are potential risk factors for the development of postembolization syndrome after hepatic transarterial chemoembolization for hepatocellular carcinoma.